Studi Keamanan Pangan Kimiawi dari Logam Berat Timbal pada Euthynnus Sp , di Perairan Semarang. - Widajanti, Laksmi; Girsang, Rohdearni; Pradigdo, Siti Fatimah (Jurnal Kesehatan Lingkungan Indonesia, 2004)
ABSTRACT Background: One of the impact of industrial development is the decreasing water quality that may cause pollution of living resources,especially the fish. The objective of this research is to determine the consentration of lead (Pb) Euthynnus sp. and to analize its  chemical safety in the coast  Semarang.  Methods:  This study  is a descriptif research with a cross sectional approach. The 30 samples of Euthynnus   was taken from the markets in Semarang City, including  Jatingaleh, Peterongan, Bulu, Johar, dan Rejomulyo market. Results:  The finding of this research showed that the highest  Lead consentration in Euthynnus Sp was 2,51 ppm and the lowest was  0 ppm  with the average of  0,81 ppm  and the standard deviation was  0,91 ppm.   There was 33,3 % sample which has the concentration of Lead  more than the maximum standard. Conclusion: It was suggested to choose the fresh fish to consumed by considering the site of fish catching. It is also suggested to  the government and  the related institution in semarang City to make a regulation and policy to protect the consumer from the toxic effect of heavy metal in fish.   Key word : Euthynnus sp., heavy metal (Lead),  Coast of Semarang